Incidence of sexually transmitted diseases in rape victims during 1984. - Forster, G E (1986)
During 1984, 46 women attended the sexually transmitted disease (STD) clinic at St Mary's Hospital alleging that they had been raped. At presentation, 31 (67%) were asymptomatic. Evidence of STD was found in 14 (30%) women, mixed infections occurring in four. Chlamydia trachomatis and Trichomonas vaginalis were each detected in six (13%) patients and Neisseria gonorrhoeae in three (6%). The source of the infection could not confidently be traced to the alleged rapist. Two patients were found to have cervical cytological abnormalities suggestive of cervical intraepithelial neoplasia of grades II or III. One woman became pregnant as a consequence of the sexual assault. Investigations may unveil infection or other abnormalities, which are incidental to the rape but nevertheless require further investigation and treatment.